Analysis Of Affective Meaning In Tweets Related To Conflicts Between KNetz And Sea Netizens on X: A Semantic Study - Fitri Umayah; Diana Anggraeni; Dian Fitri K (English Lecturers and Teachers Association (ELTA), 2026)
The dispute between Korean netizens (KNetz) and Southeast Asian netizens (SEAblings) on Platform X (formerly Twitter) has attracted considerable attention due to the widespread use of emotionally and racially charged language. This cross-cultural online conflict provides a valuable context for examining how affective meanings are constructed and expressed in digital interactions. The conflict has generated various affective meanings that reflect users' attitudes and emotions toward the opposing side. Therefore, this study aims to identify the forms of affective meaning expressed in KNetz and SEAblings' tweets and examine how their linguistic functions are constructed through word choice. The study employed a descriptive qualitative method using 79 tweets selected through purposive sampling based on predefined inclusion and exclusion criteria. The tweets were identified using hashtags and keywords related to the conflict. The analysis was based on Leech's (1981) theory of meaning and language functions, focusing on expressive, directive, and aesthetic functions to identify affective meaning function. The findings show that the expressive function predominated in both groups, accounting for 80.0% of KNetz’s tweets and 79.6% of SEAblings’ tweets. The aesthetic function appeared in 43.3% of KNetz tweets and 36.7% of SEAblings tweets, while the directive function appeared in 15.7% of KNetz tweets and 16.3% of SEAblings tweets. These findings indicate that both groups utilize the expressive function through insults, profanity, and sarcasm to convey anger, hatred, and contempt toward the opposing group. This suggests that language in digital conflicts serves not only to exchange information but also to express strong emotional attitudes. Keywords : Affective meaning; Semantic; language function; social media X